The design politics of the passport materiality, immobility, and dissent - Keshavarz, Mahmoud (Bloomsbury Visual Arts, 2020)
The Design Politics of the Passport presents an innovative study of the passport and its associated social, political and material practices as a means of uncovering the workings of 'design politics'. It traces the histories, technologies, power relations and contestations around this small but powerful artefact to establish a framework for understanding how design is always enmeshed in the political, and how politics can be understood in terms of material objects. Combining design studies with critical border studies, alongside ethnographic work among undocumented migrants, border transgressors and passport forgers, this book shows how a world made and designed as open and hospitable to some is strictly enclosed, confined and demarcated for many others - and how those affected by such injustices dissent from the immobilities imposed on them through the same capacity of design and artifice
Keywords: Design; Politik; Pass; Passports / Design; Design / Political aspects